Eksistensi Yayasan Amal Saleh Tahun 1985-2022 : Inisiator Aktivis YAS - Fera Geni; Abdul Salam (Jurusan Sejarah FIS UNP, 2023)
This study discusses the background of the emergence of yayasan amal saleh, in management of yayasan amal saleh: the initiators of the YAS activist and the social impact of the foundation's establishment. The purpose of this study is to explain the emergence of yayasan amal saleh, explain the management of a yayasan amal saleh and analyze the social impact of the establishment of a yayasan amal saleh in the city of Padang in 1985-2022. This study uses historical methods, namely: Heuristics or data collection in the form of interviews with founders, administrators, alumni and activists as well as secondary data sources. After that, testing and evaluating the data collected through internal and external criticism, after that interpretation and the final stage is writing history. The results of the research show that the idea of ​​the foundation from Mr. Mochtar Naim was the beginning of the foundation. The Amal Saleh Foundation was founded by Mr. Mochtar Naim, Asrul Lukman, Yusda, Hendri, Yasir Eri and Zulhedi. The emergence of a foundation began with a group of teenagers who had the same vision and mission and had a social and humanitarian spirit. The establishment of the foundation has an impact on society, be it in the religious, social, humanitarian and educational fields. The existence of a pious charity foundation is very much influenced by the community, YAS activists and alumni, where activities in the foundation are managed by YAS activists and assisted by alumni.